Analisis Estimasi Waktu Penyelesaian Proyek Perangkat Lunak Menggunakan Metode PERT - Gentisya Tri Mardiani (@is The Best : Accounting Information Systems and Information Technology Business Enterprise, 2018)
Planning the schedule on the construction project software in general is based on experience from a previous project, so that in determining the duration of work using only one of the estimate, or the duration for every job has been set directly by the Project Manager or Project Team in the company. This resulted in when the construction project, when there was the problem of lack of progress, Project Manager of not knowing the possibility of whether the project can continue to run as planned or not. In addition, the determination of one of the estimate for the duration of work not suitable with the characteristics of the software, because in the construction project software there is still uncertainty in the time the completion of projects. The weakness in the use of the value of the estimated duration of is when there are problems that can not be predicted with certainty the length of it, resulting in the duration of work has been set for later employment should be set back, causing projects to be too late. Based on the problem needed an analysis to determine the probability of the completion of projects using the method of program Evaluation and Review Technique (PERT), this method employs three estimates of the duration of the duration of optimistic, the duration of the most likely and the duration of the pessimistic. It is expected to know the time the completion of projects, Project Manager can do the planning of the scheduling of the project. The result of this study shows that the probabilities of the completion of projects can be counted when Project Manager already know the duration of the critical of the schedule the construction project.